What's the message? A content analysis of newspaper articles about assisted reproductive technology from 2005 to 2011. (June 2014) - King, L.; Tulandi, T.; Whitley, R.; Constantinescu, T.; Ells, C.; Zelkowitz, P.
Abstract Infertility and its treatment is the subject of considerable media coverage. In order to evaluate the representation of assisted reproductive technology (ART) in the popular media, we conducted a content analysis of North American newspaper articles. We also explored whether different themes emerged in relation to the implementation of public funding for ART in Quebec, Canada. Print and online newspaper articles from 2005 to 2011 were retrieved using the terms "in-vitro fertilization", "infertility treatment", "assisted reproductive technology", and "IVF treatment". Totally, 719 newspaper articles met inclusion criteria and were coded according to predetermined categories. Risks (63%) and ethical issues (61%) related to ART were most commonly featured. Quebec-based articles were mostly concerned with the politics and financial issues governing ART, and were less likely to report the risks and emotional impact of ART than other North American press. Newspapers tended to emphasize extreme scenarios as well as controversial cases that may not represent the everyday realities of ART. Changes in public policy may also engender shifts in the tone and content of media reports. It is important to establish resources that can inform the public as well as prospective infertility patients about their condition and potential treatment options.